The role of asymmetric dimethylarginine (ADMA) and leptin in hypertensive patients - Atamer, A.; Ilan, N.; Kocyigit, Y.; Toprak, G.; Ozbay, M.; Celik, Y. (Elsevier Ireland Ltd, 2007)
[Abstract Not Available]
76th Congress of the European-Atherosclerosis-Society -- JUN 10-13, 2007 -- Helsinki, FINLAND
Keywords: hypertension; leptin; ADMA; insulin resistance; MDA; lipoproteins